Analysis of the professors and students lived experiences of Birjand Farhangian University - Faramarz Ravanjo, Mohammad Mazidi, Mahbobeh Foladchang, Mohammadhasan Karimi, (Opción, 2019)
This research analyzed the lived experiences of the professors and students of Birjand Farhangian University with participatory learning in order to offer a practical model to the curriculum of this university. This qualitative research employed a phenomenological approach. Findings of this research showed that despite the fact that instructors expressed participatory teaching as an effective tool for enhancing cooperation between instructors and their professional development. In conclusion, the experiences of the students and professors can be classified into four categories of advantages, disadvantages, assessment and principles. Finally, some points were offered to improve the participatory learning method.